ANALYSIS OFTHIOCYANATE ON URINE AS MONITORING METHOD OF POTENTIAL GAKI (IODINE DEFICIENCY DISORDERS) BASED ON TEST KIT - Yulia Dwi Cahyani; Mike Nur Izzati; M Dzulfahmi Ramadhan (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2015)
The aim of the researh is to analyse of thiocyanate on urine. In this research, thiocyanate is oxidized by hypochlorite to cyanide that can react with ninhydrin to form a red complex compound called hydrindantin. The color intensity of red hydrindantin is proprotional to thiocyanate concentration. The higher thiocyanate concentration then the higher color intensity is. The optimum condition to form hydrindantin, such as pH, concentration of hypochlorite, and time stability of hydrindantin formation was studied using spectrophotometry at maximum wavelength of 489.50nm. The optimum condition for hydrindantin complex were pH of 10, concentration of hypochlorite of 0.05M, and the time stability of hydrindatin is 15 minutes. The proposed test kit can be used to determine thiocyanate concentration at range of 1-10ppm. The test kit has been applied to synthetic sample and urine, also compared the result to those obtained from standard spectrophotometric method to based formation of complex Fe(SCN)2+.